Screening of some Bangladeshi medicinal plants for in vitro antioxidant, antimicrobial and insecticdal activities - Shoyeb, Md. (BRAC University, 2012)
This thesis is submitted in a partial fulfillment of the requirements for the degree of Masters of Science in Biotechnology, 2011